Fairchild Turns 50 [News]. - Moore, S.K.
Fairchild Semiconductor celebrates 50 years in the business. Fairchild itself was purchased by National Semiconductor, of Santa Clara, Calif., in 1987. Ten years later it was spun out as an independent company, focused on power-related chips and headquartered at one of Fairchild's original manufacturing sites in South Portland, Maine.
Keywords: Fairchild Semiconductor industry; South Portland manufacturing sites; Power-related chips; Time 50 yr